Diet Quality Profile among Urban Elderly in Jakarta during COVID-19 Pandemic in Indonesia - Nanda Fauziyana; Novi Silvia Hardiany; Erfi Prafiantini (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2022)
Background: Insulin resistance is a condition in which insulin cannot take up glucose, increasing blood glucose. Elderly people are more exposed to insulin resistance, requiring dietary interventions that extend longevity. Trehalose, a naturally occurring sugar, showed potentially reduce insulin resistance which can be measured using the HOMA-IR (Homeostatis Model Assessment-Insulin Resistance) index. Objectives: This study aimed to assess HOMA-IR levels as a parameter of insulin resistance in old rats after giving trehalose sugar. Methods: Experimental research with 28 male Wistar rats (Rattus novergicus) was separated into 4 groups, the control group of young rats (Group A), the control group of old rats (Group B), a group of old rats that were given 2% Trehalose solution (Group C), and a group of old rats that given 2% sucrose solution (Group D) that observed for 8 weeks. Results: The results showed differences in HOMA-IR levels (p<0.001) between old and young subjects. The intervention in Group C was optimal in reducing levels of HOMA-IR (p<0.001) by 18.2% compared with the old control, while Group D increased levels of HOMA-IR by 14.3% (p<0.001) compared with the old control. The age of the subjects with HOMA-IR level is positively correlated (p<0.001; r=0.721) and the weight of subjects with the HOMA-IR level is also positively correlated (p<0.001; r=0.698), indicating that the older and the greater weight of subject resulting in the bigger of HOMA-IR value. Conclusion: Trehalose is effective in reducing HOMA-IR levels as a parameter of insulin resistance in old rats.